2021
DOI: 10.1039/d1ob01830b
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous copper-catalyzed synthesis of diaryl sulfones

Abstract: A carbon-supported copper nanoparticle (Cu-NP) with high catalytic activity for the synthesis of diaryl sulfones is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…As for those lower yields in Table 2, there are two major side reactions: deboronation/oxidation of arylboronic acids to simple arene/phenol via organometallic intermediates [19] . Deboronation was also observed in our recent work in which naphthalen‐2‐ylboronic acid was found to be coverted to naphthalene in the presence of copper catalyst [20] . For current reaction, deboronation was dominant pathway for 1 h and 1 r , as simple arenes were isolated in the reactions.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…As for those lower yields in Table 2, there are two major side reactions: deboronation/oxidation of arylboronic acids to simple arene/phenol via organometallic intermediates [19] . Deboronation was also observed in our recent work in which naphthalen‐2‐ylboronic acid was found to be coverted to naphthalene in the presence of copper catalyst [20] . For current reaction, deboronation was dominant pathway for 1 h and 1 r , as simple arenes were isolated in the reactions.…”
Section: Methodssupporting
confidence: 78%
“…[19] Deboronation was also observed in our recent work in which naphthalen-2-ylboronic acid was found to be coverted to naphthalene in the presence of copper catalyst. [20] For current reaction, deboronation was dominant pathway for 1 h and 1 r, as simple arenes were isolated in the reactions. It is also found that 1 m did not work for the reaction because it is not soluble in common solvents.…”
mentioning
confidence: 88%
“…Simultaneously, Pandey et al., [21] have reported another approach employing copper acetate hydrate for the cross‐coupling reaction between sulphonyl hydrazides and aryltriazenes providing unsymmetrical sulphones and employed Brønsted acidic ionic liquid as promoter under ambient conditions. Recently, Gong and co‐workers [22] reported a heterogeneous copper‐catalysed synthesis of diaryl sulphones, employing a carbon‐supported copper nanoparticle (Cu‐NP) with high catalytic activity. Despite of the variety of methods known for synthesis of sulphone, the majority of these approaches suffer from or the other limitations such as exorbitant materials, poor substrate scope, longer reaction span, and harsh conditions.…”
Section: Introductionmentioning
confidence: 99%